2013
DOI: 10.4103/2152-7806.116425
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of traumatic extra dural hematoma in children: Experiences and analysis from 24 consecutively treated patients in a developing country

Abstract: Background:Children with epidural hematoma (EDH) present differently than adults. The outcome of treatment is also different. We aim to report our experiences with EDH in pediatric age group in terms of mode of injury, presenting features, management, and outcomes. We also aim to identify different prognostic indicators in pediatric patients with EDH.Methods:We prospectively collected data from 24 consecutively surgically treated pediatric patients. The data collected included presenting features, radiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
8
1
Order By: Relevance
“…In our study, it is found that most common presenting symptom was vomiting found in 80% ( n = 52) cases and next to it was altered sensorium found in 70.76% ( n = 46) which is not consistent with other literature like Chowdhury et al ,[ 1 ] Khan et al ,[ 2 ] Paiva et al ,[ 3 ] Jamjoom et al [ 6 ] Early posttraumatic seizure was found in only 5 (7.6%) cases which was too low as compared to Chowdhury et al [ 1 ] but high enough as compared to Khan et al [ 2 ] one case had presented with right-sided hemiparesis and one case had left facial nerve paresis. Pupillary abnormality like bilateral dilated pupil with sluggish reaction to light was found in 2 cases.…”
Section: Discussioncontrasting
confidence: 80%
See 4 more Smart Citations
“…In our study, it is found that most common presenting symptom was vomiting found in 80% ( n = 52) cases and next to it was altered sensorium found in 70.76% ( n = 46) which is not consistent with other literature like Chowdhury et al ,[ 1 ] Khan et al ,[ 2 ] Paiva et al ,[ 3 ] Jamjoom et al [ 6 ] Early posttraumatic seizure was found in only 5 (7.6%) cases which was too low as compared to Chowdhury et al [ 1 ] but high enough as compared to Khan et al [ 2 ] one case had presented with right-sided hemiparesis and one case had left facial nerve paresis. Pupillary abnormality like bilateral dilated pupil with sluggish reaction to light was found in 2 cases.…”
Section: Discussioncontrasting
confidence: 80%
“…Fall from height was the most common mode of injury found in 44.4% ( n = 29), followed by RTA 35.35% ( n = 23) in our series is comparable with many series studies. [ 1 2 6 8 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations